18F-FDG-Uptake in Mediastinal Lymph Nodes in Suspected Prosthetic Valve Endocarditis: Predictor or Confounder? - Hove, Derk ten; Sinha, Bhanu; Glaudemans, Andor W. J. M.; Gomes, Anna; Swart, Laurens E.; Tanis, Wilco; Budde, Ricardo P. J.; Slart, Riemer H. J. A. (Frontiers in Cardiovascular Medicine, 2021)
Introduction Prosthetic valve endocarditis (PVE) is a serious disease affecting approximately 0.4% of prosthetic valve recipients per year. 18F-FDG-PET/CT has high sensitivity and specificity for PVE and is included as major criterion for the diagnosis in recent guidelines of the European Society of Cardiology. We addressed the question whether increased FDG-uptake in mediastinal lymph nodes could help to support the visual diagnostic assessment of PVE. Methods In this sub-analysis of a previously published retrospective multicentre study, 160 unique patients were identified who underwent 18F-FDG-PET/CT for evaluation of suspected PVE. 18F-FDG-PET/CT was performed in adherence to the European Association of Nuclear Medicine guidelines of 2015 and scans were assessed for signs of mediastinal lymph node activity by 2 experienced nuclear medicine physicians who were blinded to clinical context. Clinical diagnosis of PVE had been established based on surgical findings or multidisciplinary consensus after a 1-year follow-up in 80 of 160 patients (50%). Results In total, 52 patients showed increased mediastinal lymph node activity. Mediastinal lymph node activity on 18F-FDG-PET/CT did not increase diagnostic accuracy when added to the visual analysis of scans for signs of PVE: X2: 0.118, p=0.731). After excluding patients with known confounders for 18F-FDG-PET/CT, namely use of Bioglue® during prosthetic valve implantation and C-reactive protein levels below 40 mg/L, mediastinal lymph node activity was still not of additional diagnostic value compared to visual analysis alone (X2:0.129, p=0.723). Discussion Assessment of mediastinal lymph node activity did not improve 18F-FDG-PET/CT diagnostic accuracy for suspected PVE compared to visual assessment of the valve alone, as it seems to be a rather aspecific finding, that might be caused by sternal wound or mediastinal infections or even by subclinical respiratory infections. Future studies might elucidate whether increased FDG active lymph nodes indicate a high-risk patient group and whether more detailed assessment of mediastinal lymph nodes could improve their additional diagnostic benefit.